2016
DOI: 10.1111/cea.12759
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of melanocortin 1 receptor in allergic rhinitis in vitro and in vivo

Abstract: MC1R-positive basophils accumulate in the nasal mucosa of patients with AR after nasal allergen provocation. Since α-MSH suppresses proinflammatory effector functions in human basophils via the MC1R, it constitutes an interesting novel target for modulating the allergic inflammatory response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…MC1R, a G-protein coupled receptor, has gained attention due to its roles in a number of important physiological processes, including modulation of skin color, defense behavior and inflammatory responses [31,32]. For example, Johannes et al found increased protein and mRNA levels of MC1R on murine podocytes which were treated with puromycin [33].…”
Section: Discussionmentioning
confidence: 99%
“…MC1R, a G-protein coupled receptor, has gained attention due to its roles in a number of important physiological processes, including modulation of skin color, defense behavior and inflammatory responses [31,32]. For example, Johannes et al found increased protein and mRNA levels of MC1R on murine podocytes which were treated with puromycin [33].…”
Section: Discussionmentioning
confidence: 99%
“…With the growing body of evidence demonstrating the role of MC1R regulation in the treatment of allergic rhinitis and asthma, the effect of α-MSH supplementation in immunological regulation in allergic conjunctivitis has been recently explored [113,114]. Kleiner et al demonstrated that, upon allergen exposure, patients with allergic rhinitis had an accumulation of MC1R-positive basophils in the nasal mucosa.…”
Section: α-Msh Application In the Corneamentioning
confidence: 99%
“…Kleiner et al demonstrated that, upon allergen exposure, patients with allergic rhinitis had an accumulation of MC1R-positive basophils in the nasal mucosa. In vitro, the upregulation of CD203c by anti-IgE was suppressed upon α-MSH supplementation [113]. Webering et al showed that the neutralization of α-MSH in a murine model of asthma led to increased mucus production and airway inflammation.…”
Section: α-Msh Application In the Corneamentioning
confidence: 99%
“…5 We previously demonstrated that MC1R-expressing basophils are present in the nasal mucosa of patients with rhinitis following allergen provocation. 6 In this context, the close spatial proximity of basophils with other immune cells in the mucosal tissue permits modulation of ongoing allergic inflammation.…”
Section: To the Editormentioning
confidence: 99%